Gerður Kristný Guðjónsdóttir: „Poles“ (2019) - Olga Markelova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This publication contains selected translations into Russian from the book The Poles (Heimskaut, 2019) by Gerður Kristný Guðjónsdóttur, the contemporary Icelandic poet. Allusions to literary and historical plots in this book are of considerable interest. References to the Old Icelandic literature (Edda and sagas) are important for Gerður Kristný; there have been rather few poets in Iceland in the last decades who refer to the Old Icelandic literary heritage regularly. Gerður Kristný handles this literary material not from the national but form the universal perspective. Gerður Kristný emphasises the content of the Old Icelandic literary texts, particularly the episodes and details which are of minor importance in the original narrative; sometimes these are even absent but easily reconstructed. The approach to the Old Icelandic material in her poetry does not diff er from her approach to any other historical or literary data. Descriptions of emotions and small everyday details often occupy a prominent place in her poems. The relevant historical event or the literary plot itself are sometimes not mentioned in the poem, only the context is present, which determines the reader’s interpretation. Due to such poetic manner, those events and plots which the poems are based on are perceived as universal and current at the same time. All the poems in this collection are published in Russian for the first time.